10th International Borneo Business Conference 2022 "Diversification of Economy and Business Sustainability: Opportunities and Challenges" - Mohd Khairul Hisyam, Hassan; Nur Zaimah, Ubaidillah; Damien Iung Yau, Lee; Mohd Sabrun, Ibrahim; Nurul Syuhada, Zaidi (UNIMAS, 2022)
The theme of this conference is "Diversification of Economy and Business Sustainability: Opportunities and Challenges". In line with the support for the Malaysian government's efforts in ensuring the diversity of sources of Malaysian economic growth as well as the Sarawak state government's committed efforts especially in realizing the economic transformation at the state level to a digital economy and business sustainability, this theme was chosen to generate ideas and enable critical and analytical discussion. based on empirical studies on issues such as the financial and economic crisis that have a profound impact on global trade, finance and the economy. The scope of the conference will cover the business and economic aspects of Borneo in general and the global world in general. Topics of discussion include economic diversification, business sustainability, regional economy (BIMP-EAGA), energy economy based on renewable energy (hydrogen economy), digital economy and business, e-commerce, internet marketing, global financial management, global economy and business, global marketing, Islamic economics and finance, small and medium enterprises (SMEs), and so on.